2017
DOI: 10.1002/marc.201700275
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastrong and Tough Supramolecular Hydrogels from Multiurea Linkage Segmented Copolymers with Tractable Processablity and Recyclability

Abstract: Strong and tough synthetic hydrogels have received ever-increasing interests due to their potential applications as load-bearing structural materials. However, strong, tough, and recyclable hydrogels in different forms that can be generated by different methods according to various practical applications still remain an intrinsic bottleneck. A simple one-pot synthesis of multiurea linkage segmented linear copolymers with easy recyclability, hybridization, and processability, including compression molding, solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 31 publications
3
58
0
Order By: Relevance
“…Polymer hydrogels, which are 3D cross‐linked polymer networks with abundant water, have received great attention in various fields, including tissue engineering, sensors and actuators, water treatment, drug delivery, and so on. However, conventional hydrogels, cross‐linked by chemical cross‐linkers, usually suffer from weak mechanical properties (i.e., poor mechanical strength, low stretchability, bad toughness, and/or low recoverability) owing to their heterogeneous network structures and lack of effective energy dissipation mechanisms, which largely limits their applications in the load‐bearing fields . In recent years, different strategies have been proposed to design high strength and tough hydrogels with novel microstructures, such as nanocomposite (NC) hydrogels, double network hydrogels, ionically cross‐linked hydrogels, hydrophobically associated hydrogels, and hydrogen bonds or dipole–dipole enhanced hydrogels …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer hydrogels, which are 3D cross‐linked polymer networks with abundant water, have received great attention in various fields, including tissue engineering, sensors and actuators, water treatment, drug delivery, and so on. However, conventional hydrogels, cross‐linked by chemical cross‐linkers, usually suffer from weak mechanical properties (i.e., poor mechanical strength, low stretchability, bad toughness, and/or low recoverability) owing to their heterogeneous network structures and lack of effective energy dissipation mechanisms, which largely limits their applications in the load‐bearing fields . In recent years, different strategies have been proposed to design high strength and tough hydrogels with novel microstructures, such as nanocomposite (NC) hydrogels, double network hydrogels, ionically cross‐linked hydrogels, hydrophobically associated hydrogels, and hydrogen bonds or dipole–dipole enhanced hydrogels …”
Section: Introductionmentioning
confidence: 99%
“…However, conventional hydrogels, cross-linked by chemical cross-linkers, usually suffer from weak mechanical properties (i.e., poor mechanical strength, low stretchability, bad toughness, and/or low recoverability) owing to their heterogeneous network structures and lack of effective energy dissipation mechanisms, [9] which largely limits their applications in the load-bearing fields. [10][11][12] In recent years, different strategies have been proposed to design high strength and tough hydrogels with novel microstructures, such as nanocomposite groups on poly(acrylamide-co-acrylic acid) chains, and the gels showed a tensile strength of 3.52 MPa and a tensile strain of 21.13 mm mm −1 . Zhai et al [40] reported 3D-printed high strength poly(N-acryloyl glycinamide) (PNAGA)/Laponite NC gels with dual physical cross-linking for bone regeneration, and found that the osteogenic differentiation of primary rat osteoblast cells was promoted by PNAGA/Laponite NC gel.…”
Section: Introductionmentioning
confidence: 99%
“…When 80 wt% PEG800 or 70 wt% PEG1000 aqueous solutions were used as the outer phase, obvious gelation behaviors occurred, and the respective gelation time were 3′22″ and 2′42″ (Figure 2b1,c1), decreased with increasing water content in the outer phase due to the amphiphilic character of PUU3-12. [33] As shown in Figure 2b2,b3, in the case of 80 wt% PEG800, stable helical microfibers not only formed in tube II, but also could be maintained off-chip. However, in the case of 70 wt% PEG800, helical fibers first formed in the beginning of tube II, then immediately unfolded inside the microchannel (Figure 2c2), and thus only irregularly coiled microfibers could be obtained (Figure 2c3).…”
mentioning
confidence: 88%
“…This indicated that the formed helical structure could not be maintained outside the microchannel due to lack of gelation process. When 80 wt% PEG800 or 70 wt% PEG1000 aqueous solutions were used as the outer phase, obvious gelation behaviors occurred, and the respective gelation time were 3′22″ and 2′42″ (Figure b1,c1), decreased with increasing water content in the outer phase due to the amphiphilic character of PUU3‐12 . As shown in Figure b2,b3, in the case of 80 wt% PEG800, stable helical microfibers not only formed in tube II, but also could be maintained off‐chip.…”
mentioning
confidence: 96%
See 1 more Smart Citation